Qualitative Study of Profit Margin Determinants and Pricing Practices: An Islamic Banking Perspective - Mat Nor, Fauzias; Shaharuddin, Amir; Nawai, Norhaziah; Marzuki, Ainulashikin; Wan Abdullah, W Zainuddin (UUM Press, 2017)
The purpose of this study is to investigate and validate the determinants of profit margins and pricing practices of Islamic banking institutions in Malaysia. The key determinants and pricing approaches were extracted using a verbal protocol followed by probing of respondents. Focus group interviews were conducted with Islamic banking experts from Bank Muamalat Malaysia Berhad, CIMB Islamic Bank Berhad, Bank Islam Malaysia Berhad and Maybank Islamic Berhad. Preliminary analysis suggested some distinct outcomes in the identification of determinants and practices in pricing and bank margins for future research. This study has provided important insights for Islamic banks to improve their bank margins and profit by considering significant variables affecting profitability. Generally, the themes which emerged from the interviews concurred with findings from literature. However, the determinants that have yet to be captured in the literature are marketing strategies which include product risk, financing terms and conditions; and discretionary power. Awareness of Islamic banking products and cost of fund strategies are other important determinants of bank margins and profitability. This paper also has the potential to enhance bank margin determinants, concept, theory and practice.